2016
DOI: 10.13005/ojc/320556
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Properties of Processed Chickpea Varieties of Haryana (India)

Abstract: In present study, we investigated the nutraceutical potential of seed coat, dehulled raw dal, cooked dal, whole seed of dark coloured desi chickpea and light coloured kabuli chickpea. Locally grown varieties of Haryana (India) named HC-1 and KC-1 were under investigation. Total phenolic content, o-dihydric phenols, hydrophilic and hydrophobic phenols, flavonoid contents were determined in methanolic extracts of both cultivars. Free radical scavenging efficiencies were estimated by adoption of DPPH (2, 2-diphen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…On the basis of the present findings, it is suggested that colored chickpeas (desi) could be a potentially efficient food because their antioxidants, TPC, and TFC contents are higher than that found in light-colored seeds (kabuli type). In a previous study, it was shown that an outstanding and positive correlation exists between antioxidant activities and total phenolic contents in desi chickpea seeds (Segev et al, 2010;Rani and Khabiruddin, 2016).…”
Section: Discussionmentioning
confidence: 94%
“…On the basis of the present findings, it is suggested that colored chickpeas (desi) could be a potentially efficient food because their antioxidants, TPC, and TFC contents are higher than that found in light-colored seeds (kabuli type). In a previous study, it was shown that an outstanding and positive correlation exists between antioxidant activities and total phenolic contents in desi chickpea seeds (Segev et al, 2010;Rani and Khabiruddin, 2016).…”
Section: Discussionmentioning
confidence: 94%
“…In addition, chickpea fat is higher in polyunsaturated fatty acids, linoleic acid in particular, compared to sorghum fat, making it more susceptible to oxidation (Jukanti et al., 2012; Stefoska‐Needham et al., 2015). Chickpea also has lower total phenolics and tannin contents as compared to sorghum, which further increases the vulnerability of chickpea fat to oxidation (Gaytan‐Martinez et al., 2017; Rani & Khabiruddin, 2016). The peroxide value of the 70:30 chickpea–sorghum snack was higher ( p < .05) than that of the 60:40 blend at days 7, 14, 21, and 28 in the case of accelerated storage, and at day 56 in the case of room temperature storage.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, chickpea fat is higher in polyunsaturated fatty acids, linoleic acid in particular, compared to sorghum fat, making it more susceptible to oxidation (Jukanti et al, 2012;Stefoska-Needham et al, 2015). Chickpea also has lower total phenolics and tannin contents as compared to sorghum, which further increases the vulnerability of chickpea fat to oxidation (Gaytan-Martinez et al, 2017;Rani & Khabiruddin, 2016).…”
Section: Peroxide and P-anisidine Valuesmentioning
confidence: 99%
“…equivalents/g, the largest proportion of which is found in the seed coat (Rani & Khabiruddin, 2016). Chickpea seeds having colorful seed coats are reported to possess higher levels of antioxidant activity (Segev et al, 2010).…”
Section: Practical Applicationsmentioning
confidence: 99%
“…Chickpea contains phenolic compounds categorized as hydroxybenzoic acids, hydroxycinnamic acids, and flavonoids, all of which have antioxidant properties (Mekky et al., 2015). The total phenolics content of chickpea ranges from 1 to 19 mg gallic acid equivalents/g, the largest proportion of which is found in the seed coat (Rani & Khabiruddin, 2016). Chickpea seeds having colorful seed coats are reported to possess higher levels of antioxidant activity (Segev et al., 2010).…”
Section: Introductionmentioning
confidence: 99%